Emergency Dysrhythmias and ECG Injury Patterns - Brown, Kevin R. (Thomson Delmar Learning, 2003)
If you're new to ECG interpretation or need a basic refresher this book is for you. This text is ideal for the First Responder or beginning EMT. It follows a step by step approach to interpretation while providing information on the clinical significance of dysrhythmias and interventions. Many practice opportunities are provided to allow the student to develop their interpretation skills. An introduction to the more advanced level 12-lead interpretation is also provided